2013
DOI: 10.1155/2013/149693
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene Derivatives Carrying Urea, Thiourea, and Sulfonamide Moieties: Synthesis and Evaluation of Antibacterial and Antifungal Activities

Abstract: In the present study, some novel ferrocene derivatives carrying urea, thiourea, and sulfonamide groups were synthesized, and all compounds were characterized by spectral and elemental analyses. These compounds were screened for their antibacterial activities and also their minimum inhibitory concentration (MIC) against Gram-positive bacteria (Staphylococcus aureusandBacillus subtilis) and Gram-negative bacteria (Klebsiella pneumoniaandEscherichia coli) and antifungal activities againstSaccharomyces cerevisiaea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…7,8 The ferrocenyl unit is also known to modify the shapes of molecules as well as the physical properties such as colour, polarizability and magnetism. 9 Generally, studies on ferrocene revolve around generation of compounds that are used in materials science, 10 electrochemistry 11,12 catalysis, [13][14][15] medicinal applications [16][17][18][19][20][21][22][23][24] and nonlinear optics 25,26 amongst others. Ferrocene derivatives containing organic fragments bearing one or more heteroatoms such as sulphur, 27 nitrogen, 28 oxygen, 29 and phosphorous 30 have gained prominence.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The ferrocenyl unit is also known to modify the shapes of molecules as well as the physical properties such as colour, polarizability and magnetism. 9 Generally, studies on ferrocene revolve around generation of compounds that are used in materials science, 10 electrochemistry 11,12 catalysis, [13][14][15] medicinal applications [16][17][18][19][20][21][22][23][24] and nonlinear optics 25,26 amongst others. Ferrocene derivatives containing organic fragments bearing one or more heteroatoms such as sulphur, 27 nitrogen, 28 oxygen, 29 and phosphorous 30 have gained prominence.…”
Section: Introductionmentioning
confidence: 99%
“…As an important cofactor of enzymes responsible for synthesis of neurotransmitters, iron plays key role in the survival of neurons (Moos & Morgan, ). Some derivatives of urea and thiourea have been reported for possessing antiepileptic activity (Yavuz & Yıldırım, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ferrocene derivatives have been known to be effective against malaria, cancer, viral and bacterial infection (Asghar et al, ). A number of pharmacological activities including antiepileptic, analgesic, anticancerous, and antioxidant have been reported of some derivatives of urea and thiourea (Yavuz & Yıldırım, ). Ferrocene incorporated acyl urea are novel synthetic compounds that has been structurally characterized and it's bioactivity has been determined (Asghar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some thiourea derivatives are known to be associated with a wide range of biological activities such as analgesic, antitumor, antioxidant, anticonvulsant, and anti-HIV properties [ 58 66 ]. However, antibacterial and antifungal activities of thiourea derivatives have been less widely documented [ 67 69 ]. Our results based on PM microplates suggested that thiourea could be used as potential antifungal agent in heat resistant N .…”
Section: Discussionmentioning
confidence: 99%